Subject-specific axes of the ankle joint complex - Leitch, J; Stebbins, J; Zavatsky, AB (2010)
The aim of this study was to use a two-axis ankle joint model and an optimisation process (van den Bogert et al., 1994) to calculate and compare the talocrural and subtalar hinge axes for non-weight-bearing ankle motion, weight-bearing ankle motion, and walking in normal, healthy adult subjects and to see which of the first two sets of axes better fit the walking data. Motion data for the foot and shank were collected on eight subjects whilst they performed the activities mentioned. After choosing the best marker sets for motion tracking, a two-hinge ankle joint model was fit to the motion data. Ankle joint ranges of motion were also calculated. It was found that the model fit the experimental data well, with non-weight-bearing motion achieving the best fit. Despite this, the calculated axis orientations were highly variable both between motion types and between subjects. No significant difference between the fit of the non-weight-bearing and weight-bearing models to the walking data was found, which implies that either set of functional axes is adequate for modeling walking; however, the subtalar deviation angle was significantly closer for the weight-bearing activity and walking than for the non-weight-bearing activity and walking, which suggests that it is marginally better to use the weight-bearing functional motions. The results lead to questions about the appropriateness of the two-hinge ankle model for use in applications in which the behaviour of the individual joints of the ankle complex, rather than simply the relative motion of the leg and foot, is important. © 2010 Elsevier Ltd.